Computational methods in water resources - Bentley, Laurence R. | Sykes, J. F. (A.A:Balkema / Netherlands, 2000)
Table of contents: Groundwater flow in porous media; Multiphase flow; Factured media; Reactive and subsurface transport; Parameter estimation, Un certainty and inverse problems; Groundwater management. V.2 : Euleria-Lagragian local adjoint methods; Numerical methods; Scaling and heterogeneity; Coastal and estuarine flow; Flow in surface water; Watershed modeling; Surface transport